Distribution characteristics of organic matter in the Fengcheng Formation in Mahu Sag, Junggar Basin: implications for hydrocarbon generation model in alkaline lacustrine deposition - Ni, Minjie; Zhang, Yuanyuan; Tang, Yong; He, Wenjun (Frontiers in Earth Science, 2023)
Alkaline lacustrine deposits are known for their high primary productivity, unique aquatic environments, and sedimentary patterns, which are conducive to the formation and preservation of organic matter. Consequently, related source rocks have significant hydrocarbon generation potential. The study of hydrocarbon source rocks in the Fengcheng Formation of the Mahu Sag in the Junggar Basin serves as a good example for understanding organic matter enrichment and hydrocarbon generation characteristics of such alkaline lacustrine deposits source rocks. However, the characteristics of organic matter and hydrocarbon generation model in the source rocks of Fengcheng Formation lack systematic research, thus hindering exploration planning and favorable area selection. In this study, analysis of mineral content based on X-ray diffraction and organic geochemical analysis were employed, along with systematic observations of bio-precursor types under fluorescence microscopy. Based on mineral identification and quantitative statistics, the Fengcheng Formation was classified into three zones according to different alkaline mineral assemblages: an inner zone dominated by sodium carbonate minerals, a transitional zone with higher borosilicate mineral content, and a marginal zone characterized by abundant calcite deposition. The inner zone is characterized by the presence of lamalginite and telalginite, which are influenced by high pH values and changes in water depth, and exhibit high maturity characteristics. The transitional zone exhibits high total organic carbon (TOC) values, with predominantly type I and type II1 kerogen. Under fluorescence, the main components were observed to be lamalginite and telalginite, with their distribution being influenced by high salinity and ash supply. The marginal zone has relatively lower TOC than the previous two zones, which is dominated by type II2 kerogens, and contains a certain quantity of terrigenous inertinite supply. The hydrocarbon generation patterns of lamalginite and telalginite are consistent with the bimodal efficient hydrocarbon generation model observed in the source rocks of Fengcheng Formation, revealing the unique hydrocarbon generation model of organic matter in alkaline lacustrine source rocks. This research has significant implications for the exploration strategy of the alkaline lacustrine deposits in the Fengcheng Formation and similar oil- and gas-bearing basins.